Genome-wide analysis in Escherichia coli unravels a high level of genetic homoplasy associated with cefotaxime resistance. Issue 4 (12th April 2021) - Coolen, Jordy P. M.; den Drijver, Evert P. M.; Verweij, Jaco J.; Schildkraut, Jodie A.; Neveling, Kornelia; Melchers, Willem J. G.; Kolwijck, Eva; Wertheim, Heiman F. L.; Kluytmans, Jan A. J. W.; Huynen, Martijn A.
Abstract : Cefotaxime (CTX) is a third-generation cephalosporin (3GC) commonly used to treat infections caused by Escherichia coli . Two genetic mechanisms have been associated with 3GC resistance in E. coli . The first is the conjugative transfer of a plasmid harbouring antibiotic-resistance genes. The second is the introduction of mutations in the promoter region of the ampC β-lactamase gene that cause chromosome-encoded β-lactamase hyperproduction. A wide variety of promoter mutations related to AmpC hyperproduction have been described. However, their link to CTX resistance has not been reported. We recultured 172 cefoxitin-resistant E. coli isolates with known CTX minimum inhibitory concentrations and performed genome-wide analysis of homoplastic mutations associated with CTX resistance by comparing Illumina whole-genome sequencing data of all isolates to a PacBio sequenced reference chromosome. We mapped the mutations on the reference chromosome and determined their occurrence in the phylogeny, revealing extreme homoplasy at the −42 position of the ampC promoter. The 24 occurrences of a T at the −42 position rather than the wild-type C, resulted from 18 independent C>T mutations in five phylogroups. The −42 C>T mutation was only observed in E. coli lacking a plasmid-encoded ampC gene. The association of the −42 C>T mutation with CTX resistance was confirmed to be significant (false discovery rate <0.05). To conclude, genome-wide analysis of homoplasy in combination with CTX resistance identifies the −42 C>T mutation of the ampC promotor as significantly associated with CTX resistance and underlines the role of recurrent mutations in the spread of antibiotic resistance.